Executive Summary of the ASN Kidney Health Guidance on the Cardiovascular‑Kidney‑Metabolic Syndrome - Sankar D. Navaneethan; Brian Rifkin; Amy K. Mottl (Journal of the American Society of Nephrology, 2026)
Key Points The cardiovascular‑kidney‑metabolic framework encourages routine assessment of cardiovascular risk, metabolic health, and kidney function. Cardiovascular risk equations should be used in patients with CKD to direct preventive therapies and promote coordination of care to optimize outcomes. Comprehensive therapy building upon foundational CKD management is essential to minimize treatment gaps and improve cardiovascular‑kidney‑metabolic outcomes. The recent release of the inaugural AHA/ACC/ADA/ASN Guideline for the Prevention, Detection, Evaluation, and Management of Cardiovascular-Kidney-Metabolic (CKM) Syndrome calls for health care professionals across disciplines to broaden their practice to include the full spectrum of these interconnected disease states. This ASN Kidney Health Guidance aims to unite the nephrology community in this effort, highlighting the central role kidney disease plays in CKM syndrome and providing CKD-specific considerations. CKD is often complicated by comorbid cardiovascular and metabolic diseases, and regular evaluation of patients should include screening and management across disease states. The Predicting Risk of Cardiovascular Disease EVENTs (PREVENT) equation should be integrated along with kidney outcome predictors for routine patient counseling and risk assessment. Lifestyle modifications, including regular physical activity, avoidance of tobacco products, and adoption of a healthy diet and sleep patterns, underpin CKM management. Both renin-angiotensin system inhibitors and sodium-glucose cotransporter 2 inhibitors are foundational therapies in CKD for the prevention of cardiovascular and kidney end points, and glucagon-like peptide-1–based therapies and nonsteroidal mineralocorticoid receptor antagonists may be added according to an individual patient's cardiovascular and metabolic risk profile. CKM therapies may be initiated simultaneously or in rapid sequence according to shared decision making, but therapeutic inertia must be avoided. Cardiovascular disease mitigation should also include lipid management for primary and secondary prevention. Evidence supporting the benefits of CKM treatments in people with glomerulonephritis, those with kidney transplant, those on dialysis with kidney failure treated with maintenance dialysis, pediatric populations, older adults, and those with frailty is limited. However, screening and diagnosis of CKM syndrome are critical, and these cardiokidney protective therapies may be used with shared decision making. Diabetes and obesity are extremely common in people living with kidney disease; both are major contributors to CKD progression. CKD poses a major risk of cardiovascular morbidity and mortality. Hence, nephrology team members should play a vital role in the diagnosis, treatment, and implementation of a holistic and multidisciplinary approach for the well-being of patients with kidney diseases.